THU0379 REDUCTION OF ANTERIOR UVEITIS FLARES IN PATIENTS WITH AXIAL SPONDYLOARTHRITIS FOLLOWING ONE YEAR OF TREATMENT WITH CERTOLIZUMAB PEGOL: 48-WEEK INTERIM RESULTS FROM A 96-WEEK OPEN-LABEL STUDY. (2nd June 2020) - Van der Horst-Bruinsma, I.; Van Bentum, R.; Verbraak, F.; Rath, T.; Rosenbaum, J.; Misterska-Skora, M.; Hoepken, B.; Irvin-Sellers, O.; Vanlunen, B.; Bauer, L.; Rudwaleit, M.
Abstract : Background: Acute anterior uveitis (AAU), inflammation of the anterior uveal tract, is reported in up to 40% of patients (pts) with axial spondyloarthritis (axSpA). 1 AAU is associated with significant clinical burden; symptoms include blurred vision, photophobia and pain. 2 Previous studies have shown that TNF inhibitors (TNFi) can reduce AAU flare incidence in pts with radiographic axSpA, 3-5 but few have focused on pts across the full axSpA spectrum. Objectives: To analyse the impact of certolizumab pegol (CZP) treatment on AAU in pts with active radiographic and non-radiographic axSpA and a recent history of AAU. Methods: C-VIEW (NCT03020992 ) is an ongoing multicentre, open-label, phase 4 study. Pts had active axSpA according to the ASAS classification, a history of recurrent AAU (≥2 AAU flares in total and ≥1 AAU flare in the year prior to study entry), were HLA-B27 positive, and were eligible for TNFi treatment (previous failure of ≥2 NSAIDs, biologic naïve or had failed ≤1 TNFi). Pts received CZP 400 mg at Weeks (Wks) 0/2/4, then 200 mg every two wks (Q2W) to Wk 96. The primary variable was incidence of AAU flares compared to historic rates. A pre-specified interim analysis compared AAU incidence in the 48 wks prior to CZP treatment with the 48 wks of treatment, using Poisson regression adjusted for possible within-pt correlations, with period (pre- and post-baseline) and axSpA disease duration as covariates. Incidence rates (IR) were calculated based on the number of cases/pts at risk over 48 wks. Observed data are reported. Results: Of 115 enrolled pts, 89 initiated CZP treatment; 85 completed Wk 48. Baseline characteristics are shown in the Table . The 48-wk interim analysis revealed significantly fewer AAU flares/pt during CZP treatment vs before treatment (Figure ; Poisson-adjusted IR: 0.2 vs 1.5, p<0.001). The number of pts experiencing 1 and ≥2 AAU flares (64.0% and 31.5% respectively) substantially reduced during CZP treatment (12.4% and 2.2%). After 48 wks CZP treatment, disease activity improved substantially (mean ± SD Ankylosing Spondylitis Disease Activity Score [ASDAS]: 2.0 ± 0.9; Bath Ankylosing Spondylitis Disease Activity Index [BASDAI]: 3.3 ± 2.1), with 31.4% pts achieving ASAS partial remission and 29.1% ASDAS major improvement. No new safety signals were identified. Conclusion: In this open-label study, AAU flare rate significantly reduced in axSpA pts with a history of recurrent AAU during the first 48 wks of CZP. Pts also experienced substantial improvements in axSpA disease activity. References: [1]Martin TM. Curr Opin Rheumatol 2002;14:337–41 [2]Bacchiega ABS. Rheumatology (Oxford) 2017;56:2060–7 [3]van der Heijde D. Rheumatology (Oxford) 2017;56:1498–509 [4]van Bentum RE. J Rheumatol 2019;46:153–9 [5]van Denderen JC. J Rheumatol 2014;41:1843–8 Acknowledgments: This study was funded by UCB Pharma. Editorial services were provided by Costello Medical. Disclosure of Interests: Irene van der Horst-Bruinsma Grant/research support from: AbbVie, Novartis, Eli Lilly, Bristol-Myers Squibb, MSD, Pfizer, UCB Pharma, Consultant of: AbbVie, Novartis, Eli Lilly, Bristol-Myers Squibb, MSD, Pfizer, UCB Pharma, Rianne van Bentum: None declared, Frank Verbraak Grant/research support from: Bayer, Novartis, IDxDR, UCB Pharma, Consultant of: Bayer, Novartis, IDxDR, UCB Pharma, Thomas Rath Grant/research support from: AbbVie, Bristol-Myers Squibb, Chugai, Eli Lilly, MSD, Novartis, Pfizer, Roche, UCB Pharma, James Rosenbaum Consultant of: AbbVie, Corvus, Eyevensys, Gilead, Novartis, Janssen, Roche, UCB Pharma; royalties from UpToDate, Maria Misterska-Skora: None declared, Bengt Hoepken Employee of: UCB Pharma, Oscar Irvin-Sellers Employee of: UCB Pharma, Brenda VanLunen Employee of: UCB Pharma, Lars Bauer Employee of: UCB Pharma, Martin Rudwaleit Consultant of: AbbVie, BMS, Celgene, Janssen, Eli Lilly, MSD, Novartis, Pfizer, Roche, UCB Pharma